Building an integrated communication environment - Sousa, Pedro (1996)
Over the past few years, WWW has become the most successful information service on the Internet. This can be partially justified by the level of integration achieved by client software: an easy to use interface based on hyper-link navigation and a common naming convention (URLs) well supported by a multi-protocol machine (HTTP, FTP, etc). This out-of-the-box solution fulfils most of user needs, since the integration design process privileged the most commonly used set of services. A look backwards also brings up another example of success through integration: The BBS paradigm of communication. Traditional BBSs, successfully join small communities of users with common interests, offering them a way to share information, talk to each other (chat), send and receive private e-mail messages, and participate in open discussions using public messages. This paper shares the authors' recent experience in the design and development of communication environment with BBS-like functionalities, which is based upon WWW technology. Relevance is given to server side integration: a common set of data and configuration files, a set of administrative procedures and tools centred upon an HTTP server. Since many other types of on-line services may have similar requirements, in this paper the emphasis is on analyzing the imp1ementability of those communication models under WWW technology.